2005
DOI: 10.1080/01926230591034429
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Induced Atrial Thrombosis in NTP Rodent Studies

Abstract: Cardiac thrombosis, one of the causes of sudden death throughout the world, plays a principal role in several cardiovascular diseases, such as myocardial infarction and stroke in humans. Data from studies of induction of chemical thrombosis in rodents help to identify substances in our environment that may contribute to cardiac thrombosis. Results for more than 500 chemicals tested in rodents in 2-year bioassays have been published as Technical Reports of the National Toxicology Program (NTP) http://ntp-server… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 118 publications
(162 reference statements)
0
8
0
Order By: Relevance
“…Spontaneous rates of atrial thrombosis were determined for control Fischer 344 rats and B6C3F1 mice: 0% in rats and mice in 90-day studies and 0.7% in both genders of mice, 4% in male rats, and 1% in female rats in 2-year studies (Yoshizawa et al 2005). Some genetic mouse models of hyper-coagulation, abnormal myocardial contraction and dietary disorders are associated with atrial thrombosis.…”
Section: Nomenclature Diagnostic Criteria and Differential Diagnosesmentioning
confidence: 99%
See 2 more Smart Citations
“…Spontaneous rates of atrial thrombosis were determined for control Fischer 344 rats and B6C3F1 mice: 0% in rats and mice in 90-day studies and 0.7% in both genders of mice, 4% in male rats, and 1% in female rats in 2-year studies (Yoshizawa et al 2005). Some genetic mouse models of hyper-coagulation, abnormal myocardial contraction and dietary disorders are associated with atrial thrombosis.…”
Section: Nomenclature Diagnostic Criteria and Differential Diagnosesmentioning
confidence: 99%
“…atrial fibrillation) resulting in stasis of blood within the left atrial appendage (Yoshizawa et al 2005). …”
Section: Nomenclature Diagnostic Criteria and Differential Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the peroxisome proliferator-activated receptor-gamma agonist troglitazone is known to induce atrial thrombosis in Wistar rats 12 . We could not find any evidence of macroscopic thrombosis in our control Wistar rats; further, the 2-year National Toxicology Program (NTP) for rodent studies reported the incidences of atrial thrombosis in male and female F344 rats to be 4.11% and 1.01%, respectively, and those in male and female B6C3F1 mice were reported to be 0.70% and 0.68%, respectively 13 . Thus, the incidence of atrial thrombosis was clearly higher in the SPORTS rats than in other strains.…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, we observed that SPORTS rats were predisposed to the development of atrial thrombosis. Previous studies have reported that atrial thrombosis can occur following exposure to certain chemicals 13 , 14 . For instance, the peroxisome proliferator-activated receptor-gamma agonist troglitazone is known to induce atrial thrombosis in Wistar rats 12 .…”
Section: Discussionmentioning
confidence: 99%